Analytical and Stochastic Modeling Techniques and Applications 16th International Conference, ASMTA 2009, Madrid, Spain, June 9-12, 2009, Proceedings - Al-Begain, Khalid; Fiems, Dieter; Horváth, Gábor (Programming and Software Engineering, 2009)
This book constitutes the refereed proceedings of the 16th International Conference on Analytical and Stochastic Modeling Techniques and Applications, ASMTA 2009, held in Madrid, Spain, in June 2009 in conjunction with ECMS 2009, the 23nd European Conference on Modeling and Simulation. The 27 revised full papers presented were carefully reviewed and selected from 55 submissions. The papers are organized in topical sections on telecommunication networks; wireless & mobile networks; simulation; quueing systems & distributions; queueing & scheduling in telecommunication networks; model checking & process algebra; performance & reliability analysis of various systems.